2016
DOI: 10.1063/1.4962026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cavity tuning on oxygen beam currents of an A-ECR type 14 GHz electron cyclotron resonance ion source

Abstract: The effect of cavity tuning on oxygen beam currents of an A-ECR type 14 GHz electron cyclotron resonance ion source Tarvainen, Olli; Orpana, J.; Kronholm, Risto; Kalvas, Taneli; Laulainen, Janne; Koivisto, Hannu; Izotov, I.; Skalyga, V.; Toivanen, V.Tarvainen, O., Orpana, J., Kronholm, R., Kalvas, T., Laulainen, J., Koivisto, H., . . . Toivanen, V. (2016) The direct injection of intense ion beams from a high field electron cyclotron resonance ion source into a radio frequency quadrupolea) Rev. Sci. Instrum. 85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…It was concluded that changing the cavity dimensions which affects the electromagnetic field pattern of an empty cavity, as explained in Ref. 29, does not affect the dominating microwave emission frequencies which suggests that cavity properties play an insignificant role in determining the interaction between hot electrons and the instabilityinduced EM-wave. This conclusion is supported further by the simulated spectral density of TE and TM cavity modes shown in Figure 8.…”
Section: áB 1þmentioning
confidence: 99%
“…It was concluded that changing the cavity dimensions which affects the electromagnetic field pattern of an empty cavity, as explained in Ref. 29, does not affect the dominating microwave emission frequencies which suggests that cavity properties play an insignificant role in determining the interaction between hot electrons and the instabilityinduced EM-wave. This conclusion is supported further by the simulated spectral density of TE and TM cavity modes shown in Figure 8.…”
Section: áB 1þmentioning
confidence: 99%
“…In many cases this is an important channel for the loss of excess energy stored in fast particles [2,3], thereby limiting the achievement of peak plasma parameters in applications. Considering, for example, modern sources of multiply charged ions, particle ejections, which are inherent to the burst regime of cyclotron instability, that cause oscillations of the plasma potential and the beam current accompanied with a significant decrease of the average ion charge [4][5][6][7]. An explosive cyclotron instability of a mirror-confined plasma may be used for generation of high-power microwave and terahertz pulses [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this source the high charge state Pb ion beam production is maximized with B min /B ECR > 0.9 similar to our experiment in cw mode. In the pulsed operation, the instabilities are avoided at high B min because it takes several tens of milliseconds for them to appear [37] and, thus, periodic instabilities can be avoided with short pulse operation. The GTS at CERN serves as an example to demonstrate that controlling the plasma turbulence at high B min offers a route to intense beam currents of high charge state ions at several kilowatt microwave power and high power density as discussed here.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of increasing the magnetic field was explained by the appearance of periodic, 10 0 -10 3 Hz, development of electron cyclotron instabilities of the plasma that excited when B min /B ECR is above the optimal value defined by (1) [11,12]. Although the ion temperature remains relatively low (about 10 eV), the ECR heating results in formation of a strongly non-equilibrium electron distribution possessing a significant fraction of fast electrons with relativistic energies (up to 1 MeV), in addition to the 'cold' and 'warm' electron populations [13].…”
Section: Introductionmentioning
confidence: 99%